The effectiveness of the remix jump program on cardiovascular endurance in elementary school students - Resty Gustiawati; Febi Kurniawan; Citra Resita; Evi Susianti; Muhammad Surur (Universitas Nusantara PGRI Kediri, 2026)
Low cardiovascular endurance among elementary school students remains a concern in school-based physical education, particularly given limited engagement in moderate-to-vigorous physical activity. This study aimed to compare the effectiveness of the Remix Jump Program and conventional physical education in improving students' cardiovascular endurance as measured by the Bleep Test. A quantitative quasi-experimental pretest–posttest control-group design was employed, involving 20 fifth-grade students from SDN Pantai Mekar 01, Bekasi Regency, divided into an experimental group (n = 10) and a control group (n = 10). Cardiovascular endurance was assessed using the Bleep Test (Multi-Stage Fitness Test) before and after the intervention. Data were analyzed using descriptive statistics and an independent-samples t-test to compare mean gain scores between groups at the 0.05 significance level. The experimental group improved from a mean score of 6.57 to 10.45 (Δ = +3.88), whereas the control group increased from 6.08 to 7.06 (Δ = +0.21). Inferential analysis indicated a statistically significant difference in mean gain scores between groups (p < 0.05). Based on cardiovascular endurance outcomes measured by the Bleep Test, the Remix Jump Program was associated with greater improvements compared to conventional physical education within the scope of the measured variable. These findings provide preliminary evidence for the contextual application of structured music-based rhythmic exercise in elementary school physical education settings.